1985
DOI: 10.1111/j.1540-8159.1985.tb05885.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Cardiac Pacing After Open Heart Surgery: Congenital Heart Disease

Abstract: A retrospective review of 6,004 patients who underwent open repair of congenital heart defects revealed that 132 patients (2.2%) required permanent cardiac pacing postoperatively. The indications for pacing were early atrioventricular (AV) block in 55%, late onset AV block in 31%, and sick sinus syndrome in 14%. A ventricular septal defect (VSD) was the most common congenital anomaly present alone or in association with other lesions in 67% of the patients. Atrial surgery accounted for 21% of the patients requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
(2 reference statements)
1
23
0
Order By: Relevance
“…Since the first surgical closure of a ventricular septal defect (VSD) in 1954, complete atrioventricular (AV) block has been well recognized as a significant complication, with an incidence ranging between 1 and 3% . Few studies, however, have identified risk factors for development of this complication …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first surgical closure of a ventricular septal defect (VSD) in 1954, complete atrioventricular (AV) block has been well recognized as a significant complication, with an incidence ranging between 1 and 3% . Few studies, however, have identified risk factors for development of this complication …”
Section: Introductionmentioning
confidence: 99%
“…S ince the first surgical closure of a ventricular septal defect (VSD) in 1954, complete atrioventricular (AV) block has been well recognized as a significant complication, with an incidence ranging between 1 and 3%. [1][2][3][4][5][6][7][8] Few studies, however, have identified risk factors for development of this complication. 1 As surgical technique has improved, there has been increased discussion regarding the optimal timing for repair, with many clinicians opting for earlier closure.…”
Section: Introductionmentioning
confidence: 99%
“…However, pacing initiated in early childhood can be anticipated to be required over a far greater time frame than that typically expected to be required in older patients with myocardial tissue or coronary diseases. Most children require ventricular pacing as a consequence of surgical correction of various congenital cardiac defects or because of inherent embryological alterations of the normal atrioventricular conduction system, such as congenital atrioventricular block (CCAVB) 7–9 . In the former, anatomic defects may be present, which ultimately effect ventricular function in deference or addition to any pacing related changes.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence of high-degree AV block or complete AV block is not observed in these children, although different studies have shown inconsistent findings (Batra et al, 2003;Gross et al, 2006). On the contrary, late onset complete AV block (> 30 days postoperatively) has been described after cardiac surgery for congenital heart disease (Goldman et al, 1985.;Liberman et al, 2008). Complete AV block was identified at a mean of 4.7 years after surgery in one study (Goldman et al, 1985), occurring as late as 16 years after cardiac surgery (Liberman et al, 2008).…”
mentioning
confidence: 95%
“…On the contrary, late onset complete AV block (> 30 days postoperatively) has been described after cardiac surgery for congenital heart disease (Goldman et al, 1985.;Liberman et al, 2008). Complete AV block was identified at a mean of 4.7 years after surgery in one study (Goldman et al, 1985), occurring as late as 16 years after cardiac surgery (Liberman et al, 2008). Close monitoring of AV conduction seems mandatory in all patients after surgery for congenital heart disease.…”
mentioning
confidence: 99%